ANALISIS PERFORMA SISTEM CLUSTER PADA PROSES DISTRIBUTED RENDERING MENGGUNAKAN OPEN SOURCE SOFTWARE - Dian Prawira (STMIK PONTIANAK, 2012)
Abstract : Animation industry in Indonesia seems to be very prosperous as can be seen from the big amount of animation production houses. However, these production houses are not supported by high end computer graphics as they require to render complex animation video since these kind of computers are very costly. Therefore, computer system which is cheap can process complex animation rendering is needed. In this research, we need to setup available PCs as cluster computer system doing the distributed rendering process and analyze its performance for many kinds of rendering tasks. The method used in this research is laboratory experiments on five computer units connected one another and clustering using DrQueue as middleware. This technique will lead to resources sharing and rendering process distribution. The results shows that, the tested cluster system of distributed rendering process can perform the computation more efficiently when done the complex animation rendering. The results shows that the value of efficiency is higher when render complex animation.Keyword: cluster, distributed rendering, paralel computing